2004
DOI: 10.1051/0004-6361:20040110
|View full text |Cite
|
Sign up to set email alerts
|

Binary corrected X-ray light curve of Cygnus X-3: Implications for the timing properties of the compact binary system

Abstract: Abstract. We study the binary corrected X-ray light curve of Cygnus X-3 using the RXTE-ASM (All Sky Monitor) data and RXTE-PCA data. We find that the X-ray template derived from the EXOSAT observations adequately explains the binary variations. Using the recently determined quadratic binary ephemeris we correct the RXTE-PCA lightcurve and obtain the power spectrum which shows distinct features of shifting towards the low frequency regime vis-a-vis the Galactic X-ray binaries. The power spectrum doesn't vary fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 32 publications
5
10
0
Order By: Relevance
“…No signal is detected above 0.1 Hz. The slope and rms noise levels of the PDS are similar to previous studies (Choudhury et al 2004; Axelsson, Larsson & Hjalmarsdotter 2009). One noticeable difference can be seen in the power spectrum #2 with a lower noise level.…”
Section: Discussionsupporting
confidence: 88%
“…No signal is detected above 0.1 Hz. The slope and rms noise levels of the PDS are similar to previous studies (Choudhury et al 2004; Axelsson, Larsson & Hjalmarsdotter 2009). One noticeable difference can be seen in the power spectrum #2 with a lower noise level.…”
Section: Discussionsupporting
confidence: 88%
“…Reig, Papadakis & Kylafis (2002) find that the power spectrum of the microquasar GRS 1915+105 is well fitted by a power law (equation 11) with index β ≃ 1 in the frequency range 10 −7 to 10 −5 Hz. A power spectrum with this slope, over the same frequency range, has been also found for the X-ray light curve of Cygnus X-3 by Choudhury et al (2004).…”
Section: Calibration From Microquasarssupporting
confidence: 67%
“…The X‐ray light curve of GRS 1915+105 has a power spectrum with amplitude P 0 ω 0 ∼ 0.02 at frequencies 10 −7 –10 −5 Hz (Reig et al 2002). An amplitude smaller by a factor of ∼10 has been measured for the X‐ray power spectrum of Cygnus X‐3 in the same frequency range (Choudhury et al 2004). However, there is evidence that the amplitude of the variability of the radio emission of these powerful microquasars is larger than that of their X‐ray emission (Nipoti et al, 2005).…”
Section: Conceptual Frameworkmentioning
confidence: 86%
“…ingale et al (1985) and was found to be well described by a power law of index β = −1.8 in the frequency range 10 −5 -0.1 Hz. This result has been more or less verified in further studies by Choudhury et al (2004;β ∼ −1.5) and Axelsson et al (2009; β ∼ −2 in the canonical, disk-dominated soft X-ray state and −1.8 in the canonical, Comptonizationdominated hard X-ray state). The PDS has no power above 0.1 Hz, a result which was discussed in Berger & van der Klis (1994; they placed an upper limit of 12% rms above 1 Hz) and subsequently in Axelsson et al (2009).…”
supporting
confidence: 60%